Neuroanatomical and Symptomatic Sex Differences in Individuals at Clinical High Risk for Psychosis - Guma, Elisa; Devenyi, Gabriel A.; Malla, Ashok; Shah, Jai; Chakravarty, M. Mallar; Pruessner, Marita (Frontiers in Psychiatry, 2017)
Abstract Sex differences have been widely observed in clinical presentation, functional outcome and neuroanatomy in individuals with a first-episode of psychosis and chronic patients suffering from schizophrenia. However, little is known about sex differences in the high-risk stages for psychosis. The present study investigated sex differences in cortical and subcortical neuroanatomy in individuals at clinical high risk (CHR) for psychosis and healthy controls (CTL), and the ir relationship to between anatomy and clinical symptoms in males at CHR. Magnetic resonance images (MRI) were collected in 26 individuals at clinical high risk for psychosis (CHR; (13 men) and 29 healthy controls (CTLs; (15 men) to determine total and regional brain volumes and morphology, cortical thickness, and surface area. Clinical symptoms were assessed with the Brief Psychiatric Rating scale (BPRS). Significant sex-by-diagnosis interactions were observed with opposite directions of effect in male and female CHR subjects relative to their same sex controls in multiple cortical and subcortical areas.. The right postcentral, left superior parietal, inferior parietal supramarginal and angular gyri (<5% False Discovery Rate (FDR) were thicker in male and thinner in female CHR subjects compared to their same-sex CTLs. The same pattern was observed in the right superior parietal gyrus surface area at the regional and vertex level. Using a recently developed surface-based morphology pipeline, we observed sex-specific shape differences in the left hippocampus (<5%FDR) and amygdala (<10%FDR). Negative symptom burden was significantly higher in male compared to female CHR subjects (p=0.04) and was positively associated with areal expansion of the left amygdala in males (<5%FDR). Some limitations of the study include the sample size, and data acquisition at 1.5 Tesla. This study demonstrates neuroanatomical sex differences in CHR subjects, which may be associated with variations in symptomatology in men and women with psychotic symptoms.